Wound-Healing Effect of Ethyl Acetate Subfraction Ointment from Meniran Leaves (Phyllathus niruri L.) at 5% Concentration on White Male Rats - Tobat, Sanubari Rela; Wahyuni, Fatma Sri; Yenny, Satya Wydya; MYH, Etriyel; Annisa, Annisa; Wardi, Epi Supri; Fendri, Sandra Tri Juli (PT. Riset Press International, 2025)
A study has been conducted on the healing effect of excision wounds using subfraction ointment of ethyl acetate of meniran leaves (Phyllathus niruri L.) with a concentration of 5% on the percentage of wound healing area, epithelialization time, and hydroxyproline levels in male white rats. This study consisted of 3 groups of rats based on ointment grouping, and each group consisted of 15 rats; from 15 rats, they were grouped again into 3 groups based on the day of taking the results of the wound healing parameters, namely days (5, 10 and 15); each group consisted of 5 rats, where group 1 was control with the administration of ointment base, group 2 was given (T® ointment) as a comparison, and group 3 was treated with the administration of the test preparation topically with subfraction ethyl acetate concentration of 5%. Each group was observed and measured for the percentage of wound healing area, epithelialization time, and hydroxyproline levels on days 5, 10, and 15. The results of data analysis using one-way ANOVA and two-way ANOVA followed by Duncan's test (SPSS 23.0) showed a significant difference between the control group and the treatment group in terms of the percentage of wound healing area, epithelialization time and hydroxyproline levels (p<0.05), so it can be concluded that the preparation of ethyl acetate subfraction ointment of meniran leaves with a concentration of 5% has an effect as an excision wound therapy.